Faktor Risiko Kejadian Gizi Buruk pada Anak Balita di Kota Kupang - Manafe, Sandy Roberto; Talahatu, Anna H.; Boeky, Daniela L. A. (Timorese Journal of Public Health, 2019)
Malnutrition in infancy can result disruption on physical growth and intelligence of children. Nutritional problems caused by socio-economic conditions, lack of knowledge about nutrition, lack of nutrient intake and disease infection. Data on the health department of the city of Kupang in 2017, cases of malnourished infants were recorded as many as 240 cases. The purpose of the study was analyze the incidence of malnutrition in children under five in Kupang City. This research is analytic survey research with case control design. Total sampling technique in the case group and systematic random sampling in the control group. The factors that partially influence the incidence of malnutrition (p-value ≤ 0,05) are maternal knowledge about nutrition, the number of family members, the level of energy adequacy, and the level of protein adequacy. Mothers who have toddlers need to pay attention to the nutritional intake of family members, especially toddlers by increasing nutrition knowledge regarding the fulfillment of energy and protein intake.